Understanding how we learn : / : a visual guide. - Weinstein, Yana, ....-; Sumeracki, Megan, ....-; Caviglioli, Oliver, ....- (London : Routledge, 2019)
This Accessible guide shows how to integrate effective, researchbacked strategies for learning into classroom practice. The book explores exactly what constitutes good evidence for effective learningand teaching strategies, how te make evidence-based judgments instead of relying on intuition, and how to apply findings from cognitive psychology directly to the classroom.
A David Fulton Book
Keywords: Cognitieve psychologie; Leren leren; Studievaardigheden